(untitled) (Ameghiniana, 2013)
The origin of the Class Amphibia is connected with one of the nu1jor events in the evolution of the animal world, viz. the. emergence of land vertebrates. With the first tetrn- :eods .begins the sequence of anagenetic changes which lend to Reptiles, to Mammals and to Man. The rise :of the evolutionary novelty represented by a vertebrate capable of succes-fully living on the land from ’a piscine ancestor, is one of the rare and meaningful phenomena of the evolutionary process belonging to the kind of anagenetic change which the author has called arogenesis. It is of great importance for students of evolution to know in what way this nrogenetic process did take place, and it is specially relevant for this purpose to have a good picture of the phylogenetic pattern af amphibian origin.? Two main kinds of theories have been proposed to account for the phylogenetic origin of the Amphibia: monophyletic theories and polyphyletic (diphyletic) theories. The autor makes a ·brief survey of the different polyphyletic views, arriving to the conclusion that one of the vai·ious· versions of this position is adequately supported by known facts. Holm- gren’s theory of the origin of the Urodela in the Dipneusta and of the remaining tetrapods in other, Crossopterygian, stock, is based upon inferences on the morphologic;:al evolution of the chiridium which are now completely disregarded because of posterior discoveries and discussions regarding the origin of tetrapod limbs. Huene’s splitting of the first tetrapods in Urodelidin and Eutetrapoda, each group being of a different origin within a protoamphibian level, was .mainly based in Gadow’s theory of the evolution of the vertebral column, a theory that cannot be maintained after the thorough critical revaluation of vertebral evolution made by Milliiuns. Additional support for his view was found by 1-Iuene in Jarvik’s theory of the origin of the Amphibia in two different stocks of Rhipidistians, but this has the same weakness, since the foundations of Jarvik’s views have been contradictecl by later 1discoveries in Crossopterygian morphology and systematics, mainly due to Vorobjevn and Thomson. In agreement with the recent conclusions of Szarsky and Parsons & Williams, the author points out that the large amount of basic homologies found in all Amphibia claiming for a monophyletic origin of the class, is in accordance witl1 the lack of any reliable /:support for the polyphyletic views. Both facts lead to the conclusion that the most pro- .,bnble hypothesis is that all the known Amphibia, living and fossil, are the result of· a cladogenetic process which begun in a common Rhipidistian ancestor. Closely connected with the problem of the monophyletic or polyphyletic odgin of the Amphibia as a class, is the question of the relationships among the three orders of living amphibians: Anura, Urodela and Apoda. The fall of the Gadowian vertebral theory and the rejection of the different polyphyletic views, have their consequences with regard to th s problem, since no support is now available for the commonly accepted classification that refers the Urodela and the Apoda to a subclass (Lepospondyla) different from the subclass (Apsidospondyla) in which are included the Anura and the Labyrinthodontia. A survey is made of the different characters that seem to connect the three living orders, emphasizing the bearing on this problem of teeth structure, middle ear morphology and the anatomy of the muscle levator bulbi. The author concludes that at the present state of knowJ,due no conclusive theory may be proposed to account for the relationships among Anura, Urodela and Apoda. It is clear for the author that the evidence in favor of the monophyletic origin of the whole class Amphibia is far more conclusive than the evidence which might be argued in support of any attempt to interpret the interrelationships of the Hying orders of the class. Nevertheless, if it is well kept in mind that any hypothesis pos- tulated to ·account for the relationships among Anura, Urodela and Apoda, at the present state of knowledge has a low degree of confidence, the author is inclined to maintain that the evidence seems to indicate a common origin for Anura and Urodela, and that the Apoda do not seem to be closely related with any of them, being more probably linked with the Paleozoic Microsaurs. This view would demand a revival of the Haeckelian concept of Lissamphibia, as a group for both Anura and Urodela; Regarding the nature of the protoliss- amphibian stock, the. author points out the relevance of the Branchiosaurs in this connection.